A Study of New Class of Star-Like Functions Associated by Symmetric p, q-Calculus. (30th October 2021) - Akbar, Khalid; Murtaza, Rashid; Adnan,; Khan, Umar; Khan, Ilyas; Fayz-Al-Asad, Md.
Abstract : As of late quantum calculus is broadly utilized in different parts of mathematics. Uniquely, the hypothesis of univalent functions can be newly portrayed by utilizing q -calculus. In this paper, we utilize our recently presented symmetric p, q -number m ˜   p, q to characterize new symmetric p, q -derivative D   p, q of analytic function f in the open unit disk U . Utilizing D   p, q, we introduce new class of analytic star-like functions and examine some fascinating results.